The efficiency of C-4 substituents in activating the beta-lactam scaffold towards serine proteases and hydroxide ion - Mulchande, Jalmira (2015)
The presence of a leaving group at C- 4 of monobactams is usually considered to be a requirement for mechanism- based inhibition of human leukocyte elastase by these acylating agents. We report that second- order rate constants for the alkaline hydrolysis and elastase inactivation by N- carbamoyl monobactams are independent of the pK(a) of the leaving group at C- 4. Indeed, the effect exerted by these substituents is purely inductive: electron- withdrawing substituents at C- 4 of N- carbamoyl- 3,3- diethylmonobactams increase the rate of alkaline hydrolysis and elastase inactivation, with Hammett p(I) values of 3.4 and 2.5, respectively, which indicate the development of a negative charge in the transition- states. The difference in magnitude between these p(I) values is consistent with an earlier transition- state for the enzymatic reaction when compared with that for the chemical process. These results suggest that the rate- limiting step in elastase inactivation is the formation of the tetrahedral intermediate, and that beta- lactam ring- opening is not concerted with the departure of a leaving group from C- 4. Monobactam sulfones emerged as potent elastase inhibitors even when the ethyl groups at C- 3, required for interaction with the primary recognition site, are absent. For one such compound, a 1 : 1 enzyme - inhibitor complex involving porcine pancreatic elastase has been examined by X- ray crystallography and shown to result from serine acylation and sulfinate departure from the beta- lactam C-4.